Teacher-led inquiry in school learning environments : leading by example - Mahat, Marian; Bradbeer, Chris (Emerald Publishing Limited, 2024)
Around the world, schools and school systems are spending billions of dollars in the design and build of learning environments that are equipped with innovative design elements. Through an iterative process of teacher-led inquiry, educators are transforming their pedagogical practice to use student-centred learning environments that are deemed to better suit the collaborative, creative, critical thinking, communication-focused characteristics required of students in a rapidly changing world. Drawing on case studies from Australia, Italy, Malaysia, New Zealand, and Singapore, Teacher-led Inquiry in School Learning Environments provides the voices, perspectives and reflections of educators as they traverse into their new learning environments whether a refurbishment, a prototype or as part of a built masterplan. Written by educators for educators, the book is a powerful form of evidence-based, job-embedded professional learning. It contributes to the ongoing development of the education profession not only by using research findings to inform teachers' practices and professional learning, but also by sharing these findings with peers, policymakers, and the broader community. The Linking Theory and Practice in Learning Environments series closes the gap between the theory and practice of learning environments by bringing together new research focused on the various aspects of learning environments.
Includes index.
Keywords: Educational change -- Case studies.; Education / Learning Styles.; Educational psychology.; elektronické knihy; electronic books